2008
DOI: 10.1111/j.1530-0277.2008.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief Intervention for Problem Drinkers in a Chinese Population: A Randomized Controlled Trial in a Hospital Setting

Abstract: Background:  Alcohol is a legal and accessible substance in Taiwan. As excessive alcohol has been linked to health and social problems, it is necessary to develop a brief, rapid, and low‐cost tool to help health care providers deal with persons in Taiwan whose alcohol consumption has become hazardous or harmful to their health.Methods:  A randomized controlled clinical trial with 6‐ and 12‐month follow‐ups was designed. Eighteen medical/surgical units at a medical center in northern Taiwan were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 19 publications
4
49
0
Order By: Relevance
“…However, no information is available from studies conducted in western countries for the prevalence of alcohol-drinking problems among family members of these patients. Our patient sample's prevalence of hazardous/harmful/dependent drinkers is consistent with that for patients' alcohol-drinking problems in Taiwan's general hospitals, i.e., 5.7% to 19.2%, depending on the unit selected [15,16]. However, our finding on patients' family members'/friends' hazardous/harmful/dependent-drinking prevalence (5.6%) is much lower than that of hazardous alcohol-drinking problems among family members of patients with alcohol-drinking problems in Taiwan (13.3%) [37].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…However, no information is available from studies conducted in western countries for the prevalence of alcohol-drinking problems among family members of these patients. Our patient sample's prevalence of hazardous/harmful/dependent drinkers is consistent with that for patients' alcohol-drinking problems in Taiwan's general hospitals, i.e., 5.7% to 19.2%, depending on the unit selected [15,16]. However, our finding on patients' family members'/friends' hazardous/harmful/dependent-drinking prevalence (5.6%) is much lower than that of hazardous alcohol-drinking problems among family members of patients with alcohol-drinking problems in Taiwan (13.3%) [37].…”
Section: Discussionsupporting
confidence: 50%
“…To manage the drinking behavior of individuals with hazardous and harmful drinking, a brief intervention [15] has proven to be effective in a Taiwanese hospital-patient population [15,22]. This brief intervention is offered to problem drinkers at four levels, based on their AUDIT score [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study assessing a brief intervention in problem drinkers found no effects of treatment at the 6-month follow-up but demonstrated significant effects of treatment at the 12-month follow-up. 42 Evidence for the delayed effects of brief interventions for alcohol use within a primary care setting was also noted in a meta-analysis. 11 It must be noted, however, that other meta-analyses have suggested that the effect of motivational interventions may peak early and dissipate quickly over time.…”
Section: Discussionmentioning
confidence: 97%